How do you evaluate e^( ( pi)/4 i) - e^( ( 11 pi)/6 i) using trigonometric functions?

1 Answer
May 26, 2017

e^(pi/4i)-e^((11pi)/6i)=(sqrt2-sqrt3)/2 + (sqrt2+1)/2i

Explanation:

There is a special formula for complex numbers that we will use to solve this problem:

e^(i theta) = costheta +isintheta

Therefore, we can rewrite this problem as:

e^(pi/4i)-e^((11pi)/6i)

=cos(pi/4)+isin(pi/4)-cos((11pi)/6)-isin((11pi)/6)

Now all we have to do is simplify.

=sqrt2/2+sqrt2/2i-sqrt3/2-(-1/2i)

=(sqrt2-sqrt3)/2 + (sqrt2+1)/2i

So e^(pi/4i)-e^((11pi)/6i)=(sqrt2-sqrt3)/2 + (sqrt2+1)/2i

Final Answer